Effects of Corporate Environmental Responsibility, CSR and CEO Shareholding on Financial Performance: Evidence from U.S.-Listed Companies - F. Hachicha (Финансы: теория и практика, 2024)
Corporate environmental responsibility (CER) plays an important role in the sustainable policies of firms and affects the behaviors of managers. For U.S. listed firms for 2010–2021, this study aims at evaluating the sustainability of investment through corporate environmental responsibility (CER) and corporate social responsibility (CSR), the complementarily or substitutability between (CER) and the CEO shareholding, and the impact on corporate financial performance (CFP).The results show that CSR efforts create a good image of the company, which subsequently enhances the credibility of its corporate environmental responsibility projects. Also, the results show the corporate environmental responsibility of U.S listed companies has a positive impact on performance. Specifically, the CEO’s shareholding serves as a mediator between corporate environmental responsibility and CFP. Moreover, the paper finds substitutability between CEO shareholding and corporate environmental responsibility, so the more the shareholding CEO is reluctant to take the risk, the more they avoid investing in corporate environmental responsibility projects. This finding will reinforce the positive effect of corporate environmental responsibility on performance. A positive relationship was recorded between CFP and the combination between CSR and CER and between CFP and the combination between CER and CEO shareholding. Taken together, our evidence suggests that CER concerns could enhance the extent of managerial learning, especially for firms experiencing greater risks. Our paper provides new evidence for the role of CER in reducing corporate risk and further confirms the importance of the corporate environment by conducting a robustness test.